Thai legal practitioners knowledge management: Communications skills, professionalism, and competency as the antecedents for success - Cherdsak Teeranantawanich; Thepparat Phimolsathien (My University, 2018)
The purpose of this research was to examine the variables contributing to Thai legal practitioners' knowledge management abilities.By means of simple random-sampling, the sample of 332 individuals was surveyed using the 72item, 7-level, Likert type agreement scale questionnaire on the study's four constructs.Confirmatory factor analysis was run prior to the structural equation model, with the analysis undertaken in LISREL 9.1.All causal factors in the model were shown to have a positive influence on knowledge management, with 92% variance of the factor affecting knowledge management (KM) (R2).Ranked in importance were communications skills (CSK), competency (COMP), and professionalism (PRO), with the total mean score of 0.96, 0.43, and 0.34, respectively.
Keywords: Legal Education and Practice Innovations